TiO2 Nanocrystal‐Framed Li2TiSiO5 Platelets for Low‐Voltage Lithium Battery Anode. (26th August 2020) - He, Di; Wang, Boya; Wu, Tianhao; Su, Heng; Zhang, Xu; Ren, Yang; Xu, Gui‐Liang; Liu, Zhiwei; Wang, Jinshu; Amine, Khalil; Yu, Haijun
Abstract: Titanium‐based anode materials are attracting considerable attention for use in high‐performance lithium‐ion batteries, but the compromised energy density caused by high voltage plateaus and unsatisfactory capacities severely retards their practical applications. Herein, a molten‐salt synthesis of Li2 TiSiO5 crystalline platelets and a subsequent selective facet modification by in situ growth of TiO2 nanocrystal frames are facilely achieved. The discharge voltage plateau at around 0.5 V renders the Li2 TiSiO5 anode safe compared with graphite and confers a high energy density compared with zero‐strain Li4 Ti5 O12 anode. With the optimized size, structure, and content of modified TiO2 nanocrystals associated with the exposed (001) plane of Li2 TiSiO5, the Li2 TiSiO5 ‐based anodes can deliver a capacity of above 300 mAh g −1, enhanced rate performance, and a capacity retention of 66% after 10 000 cycles. In situ X‐ray diffraction and ex situ transmission electron microscopy have demonstrated the structural stability of the anodes upon charge/discharge. Further theoretical calculation reveals 3D migration paths of Li + ions in Li2 TiSiO5 . The selective modification of in situ grown TiO2 nanocrystals on certain facets of crystallites opens a new door for the development of electrode materials possessing superior electrochemical properties. Abstract : Single‐crystal Li2 TiSiO5 platelets, with the assistance of in situ formed multiphase TiO2 nanocrystals, render this unique material high capacity and stability as an anode for lithium ion batteries. Further investigation reveals an insertion reaction and 3D Li + transport path inside the crystal structure.